Digital libraries: philosophies, technical design considerations and example scenarios, editado por David Stern - Cunha, Murilo Bastos da (Revista de Biblioteconomia de Brasília, 2001)
STERN, David (ed.). Digital libraries: philosophies, technical design considerations and example scenarios. New York: Haworth Press, 1999. 230 p.